Exploring the Stress Impact in the Paternal Germ Cells Epigenome: Can Catecholamines Induce Epigenetic Reprogramming? - González, Candela R.; González, Betina (Frontiers in Endocrinology, 2021)
Spermatogenesis is characterized by unique epigenetic programs that enable chromatin remodeling and transcriptional regulation for proper meiotic divisions and germ cells maturation. Paternal lifestyle stressors such as diet, drug abuse or psychological trauma can directly impact the germ cell epigenome and transmit phenotypes to the next generation, pointing to the importance of epigenetic regulation during spermatogenesis. It is established that environmental perturbations can affect the development and behavior of the offspring through epigenetic inheritance, including changes in small non-coding RNAs, DNA methylation and histones post-translational modifications. But how male germ cells react to lifestyle stressors and encode them in the paternal epigenome is still a research gap. Most lifestyle stressors activate catecholamine circuits leading to both acute and long-term changes in neural functions, and epigenetic mechanisms show strong links to both long-term and rapid, dynamic gene expression regulation during stress. Importantly, the testis shares a molecular and transcriptional signature with the brain tissue, including a rich expression of catecholaminergic elements in germ cells that seem to respond to stressors with similar epigenetic and transcriptional profiles. In this minireview, we put on stage the action of catecholamines as possible mediators between paternal stress responses and epigenetic marks alterations during spermatogenesis. Understanding the epigenetic regulation in spermatogenesis will contribute to unravel the coding mechanisms in the transmission of the biological impacts of stress between generations.